Analisis Nilai Overall Equipment Effectiveness (OEE) Pada Mesin Bartack Bagian Sewing Line Karimun - Agustinus Eko Susetyo; Wahyu Laksito Aji (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
A need to improve the world manufacturing business, in terms of equipment and u.s. is by increasing the utilization as optimal as possible before the equipment that is available .The utilization of the equipment that is available to the average manufacturing industry is half of a real machines ' ability .As the engine led to a measure damage , the process its production will influence and the most fatal been brought to a standstill the production process .Research on the sewing especially karimun line focusing on performance analysis bartack machine uses the overall effectiveness (OEE), equipment where paramenter research covering the availability of, rate the performance, rate of quality and OEE. The results of the OEE on both machine bartack obtained OEE average score of percent and percent 76 72 where the percentage has not met the standards OEE 85 percent of the world On a bartack 1 availability to value percentage 93 decision which percent where the value is already meet the standards of the world, the percentage of performance 81 decision which percent this value has not reached the world standard and quality of the percentage rate of 100 percent where the value is already meet the standards of the world, and on a bartack 2 availability to value percentage 94 decision which percent where the value is already meet the standards of the world, the percentage of performance 76 decision which percent this value has not reached the world standard and quality of the percentage rate of 100 percent where the value is already meet the standards of the world. Based on a percentage variable OEE so concluded that variable rate about a major cause of this low value and the factors causing reduced the real value OEE performance rate on a broken or the needles bartack blunt and thread